Synthesis, characterization and magnetic properties of ultrafine Co3O4 octahedra - Zhang, Hongzhou; Coey, John; Schmitt, Wolfgang; Venkatesan, Munuswamy (My University, 2015)
Octahedral Co3O4 nanoparticles were synthesised in an aqueous ammonia solution using hexagonal β-Co(OH)2 nanoplates as starting materials. Electron microscopy analysis indicates that the Co3O4 particles have diameters of 20-40 nm and adopt a well-crystallized cubic spinel structure. The octahedral habit was verified by high angle annular dark field imaging. High resolution electron microscopy results revealed that the long axis of the octahedral Co3O4 nanoparticles coincides with crystallographic <111> direction and the facets are the {111} planes. Magnetization measurements reveal antiferromagnetic ordering below 10 K, with a paramagnetic Curie temperature of 3 K and a paramagnetic susceptibility that is double that expected for high-spin Co2+. The results show that a substantial fraction of the B-site Co3+ in the nanoparticles is in a high-spin state.
PUBLISHED
Keywords: Antiferromagnetism; Electron microscopes; Electron microscopy; Lanthanum compounds; Nanoparticles; Paramagnetism; Single crystals; Antiferromagnetism; Electron microscopes; Electron microscopy; Lanthanum compounds; Nanoparticles; Paramagnetism; Single crystals; Nanoscience & Materials